Perceptions of physical education students and teachers on physical education learning - Bayu Nugraha; Suharjana Suharjana; Ria Lumintuarso (Jurnal Cakrawala Pendidikan, 2022)
Teachers are required to be aware of their students' perceptions of physical education in addition to their own perceptions of the subject's current teaching experience. The qualitative approach is the approach used in this study with the constant comparison method by coding, categorizing, and finding themes in the interview transcripts. The results of this study were designed to find out students' perceptions of physical education and teaching difficulties in 63 elementary schools in Yogyakarta, Indonesia. A cross-sectional sample included 127 students (1st to 3rd graders of the elementary schools) and their physical education teachers (n = 68). Most students agreed they like sports or physical activities (95.6%). Few students like game-based physical education activities (18.89%). Most teachers showed great perception toward multilateral movement (70.58%). Students preferred to learn physical education through games and that they believed learning the subject has brought many benefits such as having a stronger and healthier body and increasing their motivation to be an outstanding athlete. Teachers had learned multilateral movement but they were still limited by their low capacity to create engaging learning experiences and manage students in the learning processes